The Effectiveness of Core Stability Exercise Toward the Beta-Endorphin Hormon Level of Postpartum Mothers - Nahdiyah Karimah; Entan Afriannisyah (Jurnal Kesehatan Vokasional, 2025)
Background: Postpartum mothers experience a drop in beta-endorphin levels on day 4. Beta-endorphins play an important role in analgesics, milk production, and preventing postpartum depression.Objective: This study aimed to determine the effectiveness of core stability exercise on the level of beta- endorphin hormones in postpartum mothers.Methods: The research design used a pretest and posttest controlled group design. Involving 42 respondents, namely postpartum mothers at Halmahera and Ngesrep Health Centers, Semarang. Respondents were divided into 2 groups equally by simple random sampling, namely: experimental group (core stability exercise) and control group (postpartum exercise). Then the effect before and after the intervention on beta-endorphin hormone levels will be seen by controlling anxiety scores. Analysis using independent T test and MANCOVA.Results: The mean increase in beta-endorphin hormone level in the experimental group was 140 ng/ml, while in the control group it was 43.1 ng/ml. Core stability exercise is more effective for increasing beta-endorphin hormone levels after controlling anxiety compared to postpartum exercise with a p value of 0.023.Conclusion: Core stability exercise is effective in increasing beta-endorphin hormone levels in postpartum mothers. This research serves as a guideline for midwives to apply core stability exercise when providing midwifery care to postpartum mothers.